Artificial presence : philosophical studies in image theory. - Wiesing, Lambert; Schott, Nils F. (Stanford : Stanford university press, 2010)
- Image studies, image theory, and the concept of the image ##- The main currents in today's philosophy of the image ##- When images are signs: the image object as signifier ##- What could "abstract photography" be? ##- Windows, TVs, and windows again ##- Virtual reality: the assimilation of the image to the imagination ##- Plato's concept of mimesis and its concealed canon ##- What are media?
"Originally published in German in 2005 under the title: Artifizielle Präsenz: Studien zur Philosophie des Bildes.
boek